Suscetibilidade in vitro de Candida rugosa frente a antifúngicos e óleos essenciais - Ludwig, Aline (2018)
The isolation of Candida non-albicans species has increased, as well as the resistance of these yeasts to the existing antifungal. Candida rugosa (Diutina rugosa) has been considered an emerging pathogen and affects humans and animals. Assessment of antifungal susceptibility is one way of monitoring resistance and predicting appropriate therapies. In this context, the present study evaluated the sensitivity of C. rugosa isolates against fluconazole, voriconazole, ketoconazole, itraconazole, amphotericin B, nystatin, terbinafine, flucytosine, caspofungin, micafungin and anidulafungin. In addition, as a way of seeking alternatives to conventional treatments, the in vitro antifungal activity of the essential oils obtained from Origanum vulgare (oregano), Cinnamomum cassia (cassia), Rosmarinus officinalis (rosemary), Ocimum basilicum (basil), Piper nigrum (black pepper) and the compounds carvracol, thimol and cinnamaldehyde against C. rugosa. Fifteen C. rugosa strains isolated from animals (nine dogs, three cows, one equine, one coati, one hawk) were used. The broth microdilution methodology standardized by Clinical and Laboratory Standards Institute (CLSI) document M27-A3 was used to determine the Minimum Inhibitory Concentration (MIC) of the tested agents. The results showed MIC capable of inhibiting 90% of the tested strains of: 0.125 μg/mL for ketoconazole and voriconazole; 0.25 μg/mL for micafungin; 0.5 μg/mL for anidulafungin; 1 μg/mL for caspofungin; 2 μg/mL for itraconazole, flucytosine and amphotericin B; 8 μg/mL for fluconazole and 16 μg/mL for nystatin. Terbinafine was not able to inhibit the yeast growth. The compounds carvacrol, thimol and cinnamaldehyde and the essential oils of oregano, cassia and basil presented MIC ranged from 40 μg/mL to 320 μg/mL. Moreover, the essential oils of black pepper and rosemary were tested but did not present activity in the concentration used. In conclusion, the present work demonstrated the susceptibility profile of a small collection of C. rugosa isolated from animals to eleven commercial antifungals; however, it is necessary to establish species-specific breakpoints to better characterize the susceptibility. It was also shown that the oils of oregano, cinnamon cassia, basil and the compounds carvacrol, thymol and cinnamaldehyde are possible alternatives of treatment and deserve in vivo evaluation to confirm their activity against C. rugosa infections.